The influence of interpersonal harmony on sustainable consumption behavior in China from a Confucian perspective: exploring the dual-path mediating role of ethics and norms - Xin, Yuanlai; Chen, Chun-Shuo; Yang, Chaoqiao (Frontiers in Psychology, 2025)
IntroductionResource scarcity is a critical issue facing the world today. Environmentally friendly consumption is essential for achieving sustainable social development. While existing literature has predominantly examined the harmony between humans and the environment, there is limited understanding of how interpersonal harmony among individuals influences sustainable consumption behavior.MethodThis study collected survey data from 526 urban residents in China. Structural equation modeling was used to test the hypothesized relationships among interpersonal harmony, ethical evaluation, personal norms, and sustainable consumption behavior.Results(1) All scales demonstrated good reliability (Cronbach’s α > 0.70, CR > 0.70) and validity (AVE > 0.50). CFA results confirmed acceptable model fit (Srmr = 0.038, Rms theta = 0.098). (2) Interpersonal harmony had a significantly positive effect on sustainable consumption behavior. (3) Ethical evaluation played an independent mediating role between interpersonal harmony and sustainable consumption behavior. (4) Personal norms played an independent mediating role between interpersonal harmony and sustainable consumption behavior. (5) Ethical evaluation and personal norms as chain mediators in the association between interpersonal harmony and sustainable consumption behavior. (6) Environmental cognition positively moderated the relationship between ethical evaluation and personal norms.DiscussionThese findings highlight the importance of interpersonal harmony in promoting sustainable consumption behavior. Practically, the study suggests that managers and policymakers should guide consumers to cultivate harmonious cultural values and strengthen civic moral awareness to encourage sustainable consumption.